2000
DOI: 10.4049/jimmunol.165.12.7096
|View full text |Cite
|
Sign up to set email alerts
|

Synergy and Cross-Tolerance Between Toll-Like Receptor (TLR) 2- and TLR4-Mediated Signaling Pathways

Abstract: A family of Toll-like receptor (TLR) mediates the cellular response to bacterial cell wall components; murine TLR2 and TLR4 recognize mycoplasmal lipopeptides (macrophage-activating lipopeptides, 2 kDa (MALP-2)) and LPS, respectively. Costimulation of mouse peritoneal macrophages with MALP-2 and LPS results in a marked increase in TNF-α production, showing the synergy between TLR2- and TLR4-mediated signaling pathways. Macrophages pretreated with LPS show hyporesponsiveness to the second LPS stimulation, terme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
307
9
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(359 citation statements)
references
References 38 publications
34
307
9
6
Order By: Relevance
“…This was also the case for macrophages from the joints of patients with other forms of inflammatory arthritis. Further, it is possible that the reduced response by macrophages in other forms of inflammatory arthritis (compared with that by RA macrophages) may be due to greater prior in vivo activation of these macrophages in response to endogenous TLR ligands, resulting in toler-ance to a repeat challenge by microbial TLR ligands (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…This was also the case for macrophages from the joints of patients with other forms of inflammatory arthritis. Further, it is possible that the reduced response by macrophages in other forms of inflammatory arthritis (compared with that by RA macrophages) may be due to greater prior in vivo activation of these macrophages in response to endogenous TLR ligands, resulting in toler-ance to a repeat challenge by microbial TLR ligands (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, endotoxin or LPS tolerance is a well-established phenomenon in which pre-exposure to a sublethal dose of LPS blunts subsequent lethal LPS-induced mortality, and this effect was closely associated with diminished production of proinflammatory cytokines [34,35]. In addition to LPS tolerance, several non-LPS bacterial cell wall components, including bacterial lipoprotein (BLP), also induce tolerance [36,37]. Unlike LPS or BLP, however, ginsan exhibited a wide spectrum of bacterial tolerance in Gram-positive, Gram-negative, and polymicrobial septic models and did not induce lethal shock, even at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that tolerance induction is an interplay of altered conditions at several steps of signal transduction. Whereas initial findings in human cells stressed the importance of inhibitory cytokines such as interleukin (IL)-10 or transforming growth factor (TGF)-b, 31 experiments using knockout mice 14,32 and co-culture experiments 15 did not support a major contribution of these mediators. Also, while down-regulation of TLR-4 has been postulated to contribute to tolerance, 33 other reports demonstrated cellular refractoriness independent of TLR-4 regulation, 13 and no similar findings of an involvement of receptor down-regulation in cellular refractoriness were obtained for other TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12] In light of the finding that 10 cellular responses to different microbial stimuli are mediated by different 11 TLRs, studies were initiated to determine whether, in analogy to LPS tolerance, pretreatment with microbial non-LPS stimuli also induces hyporesponsiveness to subsequent restimulation. Indeed, it has been reported that stimulation with prototypical ligands for TLR-2 (+TLR-1 or -6), [13][14][15][16][17][18] TLR-4, TLR-5 19 and TLR-9 20,21 also induces this state of hyporesponsiveness towards subsequent stimulation with the same ligand. Moreover, stimuli signalling via TLR-2 and TLR-4, 14,15 as well as TLR-4 and TLR-9, 20 can substitute for each other, mediating cross-tolerance in vitro as well as in vivo.…”
Section: Discussionmentioning
confidence: 99%